Artificial Intelligence-based Medical Image Fusion Analysis for Early Detection of Alzheimer’s disease - Swathi, K. (Asian Journal of Pharmaceutics (AJP), 2025)
This research work investigated a selection of fundamental research projects that helped develop the development of medical image fusion in the initial course of study that we intended for the adaptive pulse-coupled neural network. As time progresses, Alzheimer’s disease (AD) detection affected individuals can feel the severity of the condition by finding it increasingly difficult to recall recent events, and they also find it hard to engage in logical reasoning or recognize familiar faces. The introduction and innovation in the field of advanced neuroimaging technologies have contributed to an excellent level of support for such tools in AD diagnosis. By deploying these approaches, investigators are able to understand better the complicated structural and functional relationships within the nervous system and identify the clinical alterations that mark AD. The results of these investigations not only provide an anchor for the proposed technique, but they show information on the evolution of methods regarding this area of study